Fuzzy Quantitative Analysis Method for Stock Selection into Portfolio - Wichai Witayakiattilerd (Science Faculty of Chiang Mai University, 2019)
This article proposes a fuzzy logic quantitative analysis procedure for stock selection into portfolio. This procedure uses fuzzy sets and rules that are based on past financial data that include price per earning ratio (P/E), price per book value ratio (P/BV), dividend, return-on-assets ratio, and return-on equity-ratio. An analysis of a stock in one of the industries is performed by inputting current financial data into the analysis model and the output will be investment weight for that particular stock. These weights are for sorting stocks according to their good potential and for user’s consideration before making a decision to include a stock in his or her portfolio. In this study, recent stocks of the property & construction industry in the Stock Exchange of Thailand have been analyzed as a case study.